Optimized Leasing on Mobile Devices using Dynamic Programming - Anandkumar, V; T.R, Kalaiarasan; A M, Ratheeshkumar (International Journal of Engineering and Technology, 2018)
Now a day’s all advanced mobiles uses mobile data to retrieve content from remote server through user requested queries. The request processed on the mobile devices reduces the available battery power to a significant extent. The processing of user queries at remote server gets very low response during the huge query transmission due to communication delay. In a network used mobile station scenario, the service provider is deployed by the mid network nodes with leasing capability. Leasing is the process of borrowing some resources to the mid network from the service provider. The processing cost in the mid network is low. The user queries should be processed before identifying the intended content from the remote server. The computation power used for leasing improves the response time by reducing the use of battery power on mobile devices. The low leasing cost reduces the traffic in the remote server. The response time taken to download the content from the mid network has been experimentally analyzed.